2015
DOI: 10.1109/tip.2015.2474710
|View full text |Cite
|
Sign up to set email alerts
|

Rayleigh-Rice Mixture Parameter Estimation via EM Algorithm for Change Detection in Multispectral Images

Abstract: The problem of estimating the parameters of a Rayleigh-Rice mixture density is often encountered in image analysis (e.g., remote sensing and medical image processing). In this paper we address this general problem in the framework of change detection (CD) in multitemporal and multispectral images. One widely used approach to change detection in multispectral images is based on Change Vector Analysis (CVA). Here, the distribution of the magnitude of the difference image can be theoretically modeled by a Rayleig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
45
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
3
2

Relationship

2
6

Authors

Journals

citations
Cited by 87 publications
(46 citation statements)
references
References 36 publications
0
45
0
Order By: Relevance
“…In [26], alternative approaches are mentioned. Statistical methods such as [39,60] have been used in CVA analyses. Experimental results showed that the change detection results can almost approach optimal performance using some satellite images.…”
Section: Other Approachesmentioning
confidence: 99%
See 1 more Smart Citation
“…In [26], alternative approaches are mentioned. Statistical methods such as [39,60] have been used in CVA analyses. Experimental results showed that the change detection results can almost approach optimal performance using some satellite images.…”
Section: Other Approachesmentioning
confidence: 99%
“…We will also review another interesting paper on direct subtraction. In [39], Zanetti et al analyzed the pixel magnitude distribution of the difference of two images collected at two times. The Rayleigh distribution can be used to model the magnitude of unchanged pixels, while the Rician distribution is for modeling the distribution of magnitude of change pixels.…”
mentioning
confidence: 99%
“…The purpose of DE is to obtain CD clusters with the minimum fitness value. The fitness of individual G i can be calculated using Equation (13).…”
Section: Fitness Evaluationmentioning
confidence: 99%
“…As the spatial resolution of the Landsat image is not high (≥15 m) and the intra-class variability in the image is small, pixel-based methods are suitable for Landsat image CD, which can be further divided into threshold-based or classification-based [3]. In the threshold-based method [9][10][11][12][13], it is crucial to analyze the statistical distribution of DI and find the optimal threshold to distinguish changed pixels from the unchanged ones. For example, Kittler and Illingworth proposed a minimum-error thresholding algorithm (KI), which determines the threshold by optimizing the average pixel classification error rate [11].…”
Section: Introductionmentioning
confidence: 99%
“…CVA is used together with unsupervised threshold selection techniques based on different possible models of the data distribution. For example, the Rayleigh-Rice mixture density model [9] has been recently used in the framework of the Expectation-Maximization (EM) algorithm.…”
Section: Introductionmentioning
confidence: 99%